THE EFFECT OF USING INFORMATION TECHNOLOGY AND SUPPLY CHAIN MANAGEMENT PRACTICES ON COMPANY PERFORMANCE MEDIATED COMPETITIVE ADVANTAGE COMPANY PARTNERS OF PT.BINA USAHA PRATAMA BANDA ACEH CITY - Annisa Aqila; Sofyan Idris (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2023)
The purpose of this study is to examine how the influence of the use of IT and SUPPLY CHAIN MANAGEMENT practices on company performance is mediated by competitive advantage. This study uses statistical analysis tools Structural Equation Modeling (SEM). The research population is business partners located in the city of Banda Aceh and its surroundings. The sampling technique used was census sampling with a total of 58 samples. The results of the study show that the use of IT and SUPPLY CHAIN MANAGEMENT practices have a significant effect on competitive advantage and company performance. Furthermore, the use of IT has a significant effect on Company Performance through partial Competitive Advantage mediation and SUPPLY CHAIN MANAGEMENT Practices has a significant effect on Company Performance through partial Competitive Advantage mediation.Keywords: Use of IT, SUPPLY CHAIN MANAGEMENT Practices, Competitive Advantage, Company Performance and SEM (Structural Equation Modeling) Tujuan dari penelitian ini adalah untuk menguji bagaimana pengaruh Penggunaan TI dan Praktik SUPPLY CHAIN MANAGEMENT terhadap Kinerja Perusahaan yang dimediasi oleh Competitive Advantge. Penelitian ini menggunakan peralatan analisis statistik Structural Equation Modelling (SEM). Adapun populasi penelitian merupakan mitra usaha yang berlokasi di kota Banda Aceh dan sekitarnya. Teknik sampling yang digunakan yaitu sensus sampling dengan total jumlah sampling sebanyak 58 sampel. Hasil penelitian menunjukkan bahwa Penggunaan TI dan Praktik SUPPLY CHAIN MANAGEMENT berpengaruh signifikan terhadap Competitve Advantage dan Kinerja Perusahaan. Selanjutnya Penggunaan TI berpengaruh signifikan terhadap Kinerja Perusahaan melalui mediasi Competitve Advantage secara parsial dan Praktik SUPPLY CHAIN MANAGEMENT berpengaruh signifikan terhadap Kinerja Perusahaan melalui mediasi Competitve Advantage secara parsial.Kata kunci: Penggunaan TI, Praktik SUPPLY CHAIN MANAGEMENT, Competitve Advantage, Kinerja Perusahaan dan Structural Equation Modeling (SEM)